Political opposition as an actor of the political process - Кашаба, О. Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
Political events in recent years in Ukraine indicate a problem which occurs with the opposition as a part of the political process. It is emphasized that in the public life of any democratic country, the relationships between political opponents are being built between the authorities and the opposition, that is, the opposition is an objective phenomenon of social life. The functioning of the opposition is an inherent element of the political system of any democratic state and the basis for the development of civil society.